Psychological support of persons with social anxiety disorder associated with traumatic experiences - Avramchuk, Oleksandr; Milovidova, Аліса (Psychosomatic Medicine and General Practice, 2023)
Background. Considering the high prevalence of social anxiety disorder and its impact on quality of life and occupational functioning, research aimed at effective and accessible interventions can help reduce the burden of this disorder and improve patient well-being. Understanding traumatic experiences' influence on social anxiety development is critical for developing effective interventions. Studies exploring the link between traumatic experiences and the severity of anxiety disorders can shed light on this mechanism and provide more effective support to those who have experienced trauma. One of the challenges in treating social anxiety disorder is the low readiness of individuals to seek professional help. Low-intensity interventions may become more accessible and acceptable to patients, increasing their awareness of mental health issues and motivation for self-help or seeking specialized assistance. Previous research has shown the effectiveness of specific intervention methods for social phobias, but further studies are needed to test the stability of these results over time. Considering the above, research can help improve the understanding and psychological support for individuals with social anxiety disorder and develop more accessible and effective preventive measures for patients with a history of traumatic experiences. Objective. To study the effectiveness of a low-intensity cognitive-behavioral therapy psychosocial support program for individuals with social anxiety disorder associated with a history of traumatic experiences. Materials and Methods. The study group consisted of 179 individuals who reported significant emotional and psychological discomfort due to avoiding social situations and exhibited symptoms typical of social anxiety disorder for over six months in the past. At the initial stage, 109 individuals without signs of social phobia but with limitations in social interaction, including issues with adaptation and traumatic experiences in the past, were included as a control group. The mental state was assessed using The MINI: International Neuropsychiatric Interview. Psychopathological symptoms were analyzed using self-report questionnaires and the IAPT complex scales, while the quality of life was assessed using the self-report Q-LES-Q-SF questionnaire. In the second stage of the program evaluation, data analysis was conducted solely within the leading group, excluding the control groups, based on their classification according to associated traumatic experiences. Results. In the study, for the subgroup of individuals who participated in combat, experienced immediate life-threatening situations, or witnessed such events, it was found that traumatic experiences and distress related to social avoidance accounted for 56% of the variance in overall and work-related functioning after the program and throughout one month. Depressive symptoms ceased to be statistically significant predictors after participating in the program. The reduction in the impact of traumatic experiences and anxiety-related avoidance accounted for 27% of the variance in social interaction limitations and overall distress. In the subgroup of individuals who experienced loss and were influenced by social events they considered traumatic, no initial reduction in distress related to social avoidance was observed after the interventions. However, further reduction in distress in daily life and work was associated with reduced social phobia symptoms and increased awareness and acceptance of their emotional experiences. Depressive symptoms and the impact of traumatic experiences ceased to be predictive factors for overall distress. The research confirms the importance of understanding the influence of traumatic experiences and social avoidance on the development and manifestation of comorbid conditions in social phobia during the planning and implementation of psychosocial support. Furthermore, it is considered essential to consider that the role of traumatic experiences may be mediated by the circumstances of the study's time frame. Additional research will help better understand the relationships between traumatic experiences and vulnerability to comorbid psychopathology during adaptation to emergency circumstances and develop more effective psychosocial interventions for individuals with social phobia.